Does running performance in small-sided games have a relation with postural control in youth soccer players? - Caglar Edıs; Faik Vural; Hikmet Vurgun (Türk Spor ve Egzersiz Dergisi)
Running speeds of and the distances covered by footballers during matches or small-sided games have been well determined. However, there is no study associating the properties of these parameters with the postural control properties in small-sided games (SSG). The aim of the present study was to determine the relationships between parameters designating postural control levels and running speeds in SSG. Sixteen youth players (age 17.2 ± 1.02, height 176.25 ± 0.072 cm, body mass 67.67 ± 13.27 kg) voluntarily participated in all the tests. Postural control was evaluated using one and both leg stance positions by measuring postural sway specify according to Center of Pressure (CoP) at anterior – posterior (ap) and medial – lateral directions. Movement data were collected using a 10-Hz global positioning system from games during the 1vs1, 2vs2, 3vs3 SSG, including measures of speed and the distance covered at those speeds. The main findings of our study showed a significant relationship between the running speeds of 0-6 km · h-1, 6-10 km · h-1 and 10-16 km · h-1 which can be defined as the velocities used in acceleration and direction changes and the postural parameters of CoPdap, CoPdvel,CoPndvel and CoPndvar (r-values ranging from 0.503 to 0.639) levels in 2vs2 and 3vs3 games.In conclusion, when improvement of postural control, which is a variable that can lead to an increase in athletes’ competing performances, is desired, combining practices that are designed to work out postural control parameters separately with football specific exercises (combined training) in a single training session would make significant contributions to competing performances of athletes.